2009
DOI: 10.1016/j.jpsychires.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute alcohol use on the lethality of suicide attempts in patients with mood disorders

Abstract: Acute alcohol use is an important risk factor for attempted and completed suicide. We evaluated the effect of acute alcohol intake on the lethality of suicide attempts to test the hypothesis that acute alcohol intoxication is associated with more lethal suicide attempts. This retrospective study included 317 suicide attempters enrolled in mood disorders protocols. Demographic and clinical parameters were assessed. The use of alcohol at the time of the most lethal suicide attempt was determined. On the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(44 citation statements)
references
References 43 publications
1
38
0
5
Order By: Relevance
“…Several Japanese studies have shown a favorable effect of living in a multigenerational family on women's health behaviors such as on smoking and drinking (Takeda et al, 2004(Takeda et al, , 2006 Higuchi, 2009) and other countries (Bronisch et al, 2008;Sher et al, 2009). Our analysis showed no significant association between family generation and suicide either with or without adjustment for smoking, drinking, or a history of any chronic disease, including heart disease and stress.…”
Section: Discussionmentioning
confidence: 99%
“…Several Japanese studies have shown a favorable effect of living in a multigenerational family on women's health behaviors such as on smoking and drinking (Takeda et al, 2004(Takeda et al, , 2006 Higuchi, 2009) and other countries (Bronisch et al, 2008;Sher et al, 2009). Our analysis showed no significant association between family generation and suicide either with or without adjustment for smoking, drinking, or a history of any chronic disease, including heart disease and stress.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is a close relationship between alcohol exposure and lethality of suicide attempts . In particular, such lethality increases in individuals with mood disorders (Sher et al, 2009) and, on the other hand, chronic alcohol dependence promotes depression (Yoshimasu et al, 2008): therefore the interactive effects of substance abuse and mood disorders can be considered one of the most lethal risk factors of suicide attempts.…”
Section: Studymentioning
confidence: 99%
“…The amount and type of beverage consumed, as well as the pattern of drinking, such as the excessive consumption of strong spirits, may also impact upon suicidal behaviour 47,48 . Intoxicated individuals are also reportedly more likely to attempt suicide using more lethal methods, such as firearms or hanging 49,50 .…”
Section: Factors Contributing To Suicidementioning
confidence: 99%